Editorial Special Issue TGF-Beta/BMP Signaling Pathway - Isabel Fabregat; Blanca Herrera; Aránzazu Sánchez (Cells, 2020)
The transforming growth factor β (TGF-β) superfamily plays key roles in development and tissue homeostasis, controlling the maintenance and regeneration of mature tissues [...]